Frameworks for conflict mediation in international infrastructure development: A comparative overview and critical appraisal. (1st December 2019) - Lezak, Stephen; Ahearn, Ariell; McConnell, Fiona; Sternberg, Troy
Abstract: While the extractive industries and related infrastructures are highlighted as key to economic development, they often come at a cost. Most projects involve a network of stakeholder parties; even though developers are allocating more resources to stakeholder engagement, conflict surrounding infrastructure development continues to rise. Whilst the causes of this paradox are numerous, ranging from the increasing demand for natural resources to the limited regulatory capacity of governments in the global south to oversee developers, they also highlight the lack of engagement with effective conflict resolution mechanisms. This paper undertakes a comparative review of 21 existing frameworks or "toolkits" presented by international organizations for avoiding and resolving mining-related conflicts in emerging markets. This review and analysis has four aims: i) to identify the dominant trends in frameworks that address conflict arising from the extractive industry and related infrastructural systems; ii) to identify the weaknesses and limitations of existing frameworks; iii) to assess opportunities for innovation that might increase the adoption of more effective conflict resolution strategies; iv) to forecast how existing frameworks may need to adapt and respond to emerging global shifts in development investments. Addressing these aims will contribute to a better understanding of how conflict resolution discourses, procedures, and strategies function in a sector that is critical to sustainable and equitable development.